PERFORMANCES SCOLAIRES DES ELEVES DES ECOLES SECONDAIRES DE LA COMMUNE DE LIMETE SELON LEUR ORIGINE SOCIALE - Chantal, Kadiombo Bujika Marie; Solange, Operusurusi Ondao (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
This research focuses on “Academic performance of secondary school students in the municipality of Limete according to their social origin”. The results reveal that the students surveyed from different schools in the Municipality of Limete, mainly belong to the upper social category and their average performance is higher than their peers from the working and middle social category, i.e. 67.30%. The study affirms that the socio-economic aspect has a preponderant place in the education of students, more precisely in the Municipality of Limete because there is a strong correlation between social origin and the academic performance of students.Concerning the first concern on “knowledge of the social origin of the parents of students in the Municipality of Limete”, we found that 77.9% of the subjects surveyed come from a higher social origin, while 15.7% of our sample, come from a working social origin and 6.4% belong to an average social origin.